Quantum Monte Carlo study of the transcorrelated method for correlation factors - Luo, Hongjun; Hackbusch, Wolfgang; Flad, Heinz-Jürgen (Molecular physics, 2010)
We have studied the performance of Boys and Handy's transcorrelated equation for Jastrow factors, without further approximations on the integrals involved, using quantum Monte Carlo methods. Contrary to previous statements in the literature, we observed no violation of variational bounds. Our results agree to very high accuracy with variational calculations for various atoms and small molecules. It should be mentioned that our findings are not in direct contradiction with the results of Boys and Handy obtained 40 years ago. Instead their results were slightly obscured by obvious limitations of computational resources and resulting approximations for complicated integrals. According to our results and related work, the transcorrelated method of Boys and Handy might be an interesting alternative to conventional F12 methods where the correlation factor is not the subject of optimisation.